Use multiple analysis methods to study the most important influencing factors Between the sexes and diabetes - المدرس المساعد زينب عبداهلل محمد; المدرس المساعد إسراء مؤيد علي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The multivariate statistical study deals with those views and expressed through the most influential variables in the phenomena under study, research on the link between the adopted multivariate analysis using analysis of the main components of (Principle Component method) and discriminate analysis of (Discriminate Analysis), so this research aims to determine the most important factors affecting patients infected of both Sexes with diabetes determining the number of factors derived using the analysis of the factor as well as using the distinctive analysis in the process of discrimination and classification and then estimating the best equation based on measurements and derived by the main components of discrimination between the two sexes and the comparison of results based on the ratio of error classification and show its effect on the classification process, and to achieve the search of objectives the research partition on the theoretical side was addressed to the analysis of the functioning and discriminatory analysis, the applied side included data for patients with infected of both Sexes with diabetes, obtained from (Layla Qasim Hospital) in Erbil have been reached to conclusions that we believe are important and should be noted by health providers.